Purification, crystallization and preliminary X‐ray analysis of the strawberry allergens Fra a 1E and Fra a 3 in the presence of catechin. Issue 5 (22nd May 2013) - Casañal, Ana; Zander, Ulrich; Dupeux, Florine; Valpuesta, Victoriano; Marquez, Jose A.
<x xml:space="preserve">Abstract</x> The strawberry Fra a proteins belong to the pathogenesis‐related PR‐10 protein family and share a common fold with the Bet v 1 major pollen allergen and the START/PYR/PYL proteins, which are characterized by the presence of a central cavity and are often involved in the binding of a variety of natural compounds. The Fra a proteins play a key role in the control of flavonoid biosynthesis in strawberries and are essential for pigment formation in fruits. In order to understand Fra a protein function, full‐length Fra a 1E and Fra a 3 cDNAs were cloned and expressed in Escherichia coli, and the proteins were purified to homogeneity using metal‐affinity chromatography. Diffraction‐quality crystals of Fra a 1E and of Fra a 3 in the presence of (+)‐catechin were obtained by the sitting‐drop vapour‐diffusion method. X‐ray diffraction data from single crystals of Fra a 1E and Fra a 3 were processed to 2.2 and 3.0 Å resolution in space groups P212121 and P2221, with unit‐cell parameters a = 70.02, b = 74.42, c = 84.04 Å and a = 137.91, b = 206.61, c = 174.7 Å for Fra a 1E and Fra a 3, respectively.